European Porcelain of the 18th Century as an Artifact and an Art-Object or the Compotier’s Story - Vilensky, Jan E. (Actual Problems of Theory and History of Art, 2018)
European porcelain invented in the 18th century not only became an exceptional phenomenon in decorative and applied arts, but also was significant in historical and political sense. Mysteries, intrigues, and connections with alchemy that enveloped the beginnings of European porcelain production, gave grounds to the contemporaneous preconception that the products of newly founded manufactories were particular artifacts, and apart from their practical function possessed certain cryptic meaning. Queenly porcelain sank into oblivion together with the century that had given birth to it. Around the 1820s, it was used to be known as “old” one, and “fell under scrutiny”, gradually turning from an artifact into an art object. Closer to the late 19th century, this transformation was completed and porcelain finally “occupied its special place in historical classifications”. Scrutinizing pieces of porcelain and their shapes and forms as art objects led to their higher artistic reappraisal. Since then it was only in fiction that porcelain has been presented as an artifact. The classification system is in constant need of elaboration. In the history of porcelain, there are lots of examples when an item recently taken out of a kiln, in household turned to be different from what it had been initially designed for. This could be explained by either rapidly changing vogue, or by cuisine habits, or by national specificity. The denotations of objects changed in full correspondence with this. All metamorphoses, from formal to philological, are possible to trace by taking a compotier as an example. This French word is used for shallow fruit bowls — various dishes that were part of dessert services. Special attention is to be paid to French porcelain, because, from the 1750s, France became the head “trendsetter” in this material, which was actually as new for this country as it was for others. The basic regales of a dessert course were various candied stewed fruit taken from compote. Those were placed into compotiers made of various substances, but of the greatest variety were the shapes of porcelain items. Numerous studies proved that outstanding artists and sculptors worked to create seemingly ordinary things. The origins of inspiration were quite different: from a peasant wooden saucer to coquille Saint-Jacques. In France, the proper idea of a dish for stewed candied fruit was clearly defined in the mid-18th century. In Russia, tableware was not strictly differentiated: quite various items, not only shallow fruit bowls, were called either “compotnik”, or “compotnitsa”, or designated with a loaned French word “compotier”. Thus, such a prosaic thing like compote made scholars, who seek to comply with maximum historical authenticity and classification accuracy, seriously “work out the criteria for ambiguous notions”, turning to a wide range of research approaches and methods: from art historical analysis and studies in manufactories’ registries to the inventories of service still-rooms.